Behavioral disorders practice concerns and students with EBD - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Advances in special education ;, 2012)
The area of behavioral disorders is constantly changing and advancing as a result of legislation, new trends, and current research investigations. Currently, there is no comprehensive resource that effectively covers these advances with the breath of topics as this volume. Though it is difficult to keep up with all issues and trends, this volume presents critical topics in all spheres of this area of study.